Drama with street youth: visual methodology dialogues across distance. Issue 1 (2nd January 2016) - Wager, Amanda C.; Wessels, Anne
Abstract: As past school educators and doctoral students, the authors aim to further collaborative analytical discussions across distances through the use of technology and supported readings. They describe their journey of collaboratively analyzing two different examples of data, two film clippings from an applied theatre rehearsal with street youth, while using a visual methodology to enhance their discussions. In conclusion, they explain that their analysis of this pedagogical and methodological experiment supported them as they returned to their own respective research and writing equipped with new methodological and analytical tools that facilitated seeing their own visual data differently. Through this dialogical experiment they are advocating for a fuller recognition of a collective learning methodology in education, especially in what can be the very lonely and isolating stage of analysis in doctoral research and in the beginning stages of entering the classroom.